IMPLEMENTATION OF LEGAL PROTECTION FOR WELL-KNOWN BRANDS IN INDONESIA - Lasargi Marel; Thamrin S; Abd Thalib; Syafrinaldi (International Conference On Law And Social Sciences, 2024)
In the business world, manufacturers provide distinctive signs or characteristics on their goods and services produced, commonly referred to as "brands," which are used to differentiate their production from that of others, especially for similar or related goods and services. Initially, brands were used to indicate ownership or source. Subsequently, brands functioned to indicate that a product originated lawfully from a business unit (corporation) and therefore also served to indicate that the product was made professionally. Consequently, brands have a second function, which is to serve as a guarantee of quality. The main issue in this research is the legal consequences of registering a trademark with bad faith and the legal protection of well-known trademarks based on the Supreme Court's Jurisprudence No. 022 K/N/HaKI/2002. This study is a normative research, while in terms of its nature, it is descriptive-analytical. This means that the author will provide detailed, clear, and systematic explanations regarding the implementation of legal protection for well-known trademarks in Indonesia. The Supreme Court Decision with Number 022 K/N/HKI/2002 seems to have been correctly applied to the Campina CORNETTO trademark owned by the Respondent in Cassation/Defendant, which is qualified as having substantial similarity in essence and as a whole with the CORNETTO trademark owned by the Applicant in Cassation/Plaintiff, and also qualified as riding on the well-known trademark owned by UNILEVER N.V. Therefore, the CORNETTO trademark owned by the Respondent in Cassation/Defendant must be rejected based on Law No. 20 of 2016 concerning Trademarks. Regarding the recognition of a trademark, the judge refers to the Supreme Court's jurisprudence, which is based on public knowledge. The trademark in question is obtained through promotions conducted by its owner, accompanied by evidence of the registration of the trademark in several countries. This decision also confirms that a well- known trademark that is not yet registered in Indonesia still receives legal protection in Indonesia, in accordance with Supreme Court's Jurisprudence No. 1272 K/Pdt/1984, dated January 15, 1986.